Biomechanical analysis of head injury caused by a charge explosion under an armored vehicle - Ratajczak, Monika; Fratczak, Roman; Sławinski, Grzegorz; Niezgoda, Tadeusz; Bedzinski, Romuald (Computer Assisted Methods in Engineering and Science, 2017)
In this study, the authors developed the numerical model of brain structure to assess brain injury of a person in military conditions. The numerical model aimed at analyzing changes in the mechanical parameters of brain structure in the conditions of rapid overload. The results of our investigation are intended to contribute to the explanation of the phenomena of degradation of brain structures among soldiers.